EDUCATION SYSTEM IN UK AND UZBEKISTAN - Komilova Nazirabonu Baxtiyor qizi; Zubaydova Nilufar Neʼmatullayevna; Azzamova Nigora Rajabboyevna (TADQIQOTLAR.UZ, 2024)
ANNOTATION:In this article explain some information about differences qnd resemblances of United Kingdom and Uzbekistan education system. These two countries are located in different parts of the world, but you can see the similarities and differences in the education systems of these two countries. While reading this article, you may understand why education system is important part of our life. I hope, this article will help you get some of necessary information in education